Photoshop CS3 for dummies - Bauer, Peter 1957- (Wiley Pub., 2007)
"Photoshop CS3 is a powerhouse, and here's the fast and easy way to get up to speed on all the coolest features. This friendly guide helps you get images into Photoshop - and then turn them into dazzling works of art. You'll see how to work in the right file formats, master the Brushes palette, get creative with filters, convert color to grayscale, and more!"--Resource description page
Print version record
Keywords: Adobe Photoshop; Image processing -- Digital techniques; Computer graphics; Computer Graphics; Adobe Photoshop (Computer software); Traitement d'images; Techniques numériques; Infographie; digital imaging; computer graphics; Image processing; Digital techniques